Climate change and health in medical school curricula: A national survey of medical students' experiences, attitudes and interests - Sasha Létourneau; Aishwarya Roshan; George T. Kitching; Julia Robson; Celia Walker; Chenchen Xu; Daniel Jubas-Malz; Edward Xie (Elsevier, 2023)
Background: Physicians play a critical role in addressing the health-related impacts of climate change. However, integration of education on the health effects of climate change into medical school curricula remains limited. Medical students are identified as both key stakeholders in curriculum development and leaders in curriculum change efforts. Student perspectives on the importance of learning about climate change and health are lacking and may help guide curricular growth. This study evaluates Canadian medical students' experiences, attitudes and interests related to climate change and health in medical education. Methods: A cross-sectional, population-based survey was developed, piloted and distributed to all students in Canadian medical schools who had completed ≥1 year of training by June 30, 2020. Responses were tabulated and characterized using descriptive statistics. Results: In total, 1424 eligible respondents submitted the survey, representing 12.1% of all Canadian medical students. The sample included respondents from all years of study and every school, with the majority reporting no or low engagement with climate change advocacy (70.8%). Most students believed climate change is an important determinant of health (88.0%) that will affect their future patients' health (89.6%) and that teaching on climate change should be formally incorporated into medical curricula (85.6%). A majority of students reported less teaching on climate change and health relative to other topics (85.0%) and most wanted more teaching (79.8%). Conclusions: Respondents from Canadian medical schools expressed strong interest in learning about climate change and health. Our nationwide study identifies areas for curriculum development to address the health consequences of a changing climate.